Critical racial literacy in homes, schools, and communities: Propositions for early childhood contexts. (September 2018) - Nash, Kindel; Howard, Joy; Miller, Erin; Boutte, Gloria; Johnson, George; Reid, Lisa
Grounded in critical and emancipatory theories, five critical ethnographies about the lives of children, grandchildren, colleagues, students, and teachers are analyzed and synthesized to illuminate the ways in which individuals are racially socialized over their lifespans. Three propositions for early childhood contexts were apparent across the studies: (1) racial identity and dysconsciousness are learned over time and across multiple spaces; (2) critical racial literacy is a complex, cyclical, and sometimes contradictory process; and (3) critical racial literacy demands acknowledging and confronting blind spots. Building on these propositions, the authors present implications for enacting practices that promote critical racial literacy in early childhood education settings around the globe.